The Rise of Digital Influencer on Instagram to Impact the Brand Engagement and Purchase Decision - Meta Andriani; Deasy Ariyani (Jurnal Ilmu Manajemen dan Ekonomika, 2024)
This research aims to test the effect of brand recommendations by digital influencers on purchase intentions in terms of brand engagement and brand expected value. The sample selected in this study had two characteristics: having an Instagram account and following on Instagram. The sample in this research consisted of 85 respondents and the analysis technique used in this research was the SmartPLS 4 application and the type of data collection research in this research was quantitative. The results of this research show that Perceived Influencer, Brand Engagement on Self-concept Brand Expected Value have a positive or significant influence on Intention to Purchase Recommended Brand. To increase the value of a product, the managerial implication that can be applied is that the company collaborates with digital influencers.